2013
DOI: 10.1002/rcs.1496
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of robotically controlled advanced endoscopic instruments

Abstract: This study provides evidence that the robotic control method can be implemented to improve the performance of physicians using advanced flexible endoscopes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…As a second example, robotic transapical transcatheter aortic valve implementation (TA-TAVI) devices are extremely helpful for the diagnosis and treatment of heart diseases [16,17]. In recent advancements, one of the challenging issues for TAVI is the localization and tracking problem of the valve during the cardiovascular procedure.…”
Section: Introductionmentioning
confidence: 99%
“…As a second example, robotic transapical transcatheter aortic valve implementation (TA-TAVI) devices are extremely helpful for the diagnosis and treatment of heart diseases [16,17]. In recent advancements, one of the challenging issues for TAVI is the localization and tracking problem of the valve during the cardiovascular procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that remote actuation platforms could not yet compete with the efficiency of conventional endoscope control [ 21 – 23 ]. The setup of these platforms prevented adequate scope manipulation [ 23 – 25 ]. This study shows that our setup and interface enable at least as efficient manipulation of the endoscope and effective visualization of the bowel wall.…”
Section: Discussionmentioning
confidence: 99%
“…These endoscopic devices are also not controlled intuitively and have multiple degrees of freedom which make control harder. 26 The Anubis endoscope system is one of these advanced endoscopes, and it has three degrees of freedom, insertion, rotation, and bending. The instrument is designed to be controlled manually by using a control handle that can move forwards and backwards and it can be rotated to maneuver the instrument.…”
Section: Robotically Controlled Advanced Colonoscopiesmentioning
confidence: 99%
“…The robotic controls were then tested versus the manual control of these devices by using a tapping experiment in which the operator would locate and tap on a fixed target. 26 The robotic method consists of the endoscopic device being controlled by an Omega 6 haptic device. Insertion is controlled by moving the pen forwards and backwards and the orientation of the pen controls the rotation and bending of the instrument.…”
Section: Robotically Controlled Advanced Colonoscopiesmentioning
confidence: 99%
See 1 more Smart Citation